2018
DOI: 10.1152/ajpheart.00698.2017
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high-fat diet acts on the brain to induce baroreflex dysfunction and sensitization of angiotensin II-induced hypertension in adult offspring

Abstract: Accumulating evidence indicates that maternal high-fat diet (HFD) is associated with metabolic syndrome and cardiovascular disease in adult offspring. The present study tested the hypothesis that maternal HFD modulates the brain renin-angiotensin system (RAS), oxidative stress, and proinflammatory cytokines that alter angiotensin II (ANG II) and TNF-α actions and sensitize the ANG II-elicited hypertensive response in adult offspring. All offspring were cross fostered by dams on the same or opposite diet to yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 34 publications
2
42
0
Order By: Relevance
“…Blood pressure was measured via a tail cuff ( N = 6 studies) or invasively by remote radio‐telemetry after surgical implantation of carotid artery probes ( N = 5 studies) . Effect estimates did not differ substantially between both methods.…”
Section: Resultsmentioning
confidence: 99%
“…Blood pressure was measured via a tail cuff ( N = 6 studies) or invasively by remote radio‐telemetry after surgical implantation of carotid artery probes ( N = 5 studies) . Effect estimates did not differ substantially between both methods.…”
Section: Resultsmentioning
confidence: 99%
“…ACE cleaves angiotensin I to form angiotensin II, a potent regulator of vascular function and blood volume (Dasinger et al 2016). In rodents, offspring of dams fed diets high in fat (Zhang et al 2018) and salt (Mao et al 2013) or low in protein (Watkins et al 2010) have all been shown to program offspring cardiovascular dysfunction via impaired RAS regulation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the baroreflex presents two components, the tachycardic that represents sympathetic activity and the bradycardic that represents parasympathetic activity (42,43) . In the Zhang et al (41) study, only reflex tachycardia was evaluated, whereas in the present study only reflex bradycardia was evaluated. The sympathetic dysfunction was evidenced in our present study and suggests a dysfunction in the reflex tachycardia according to data from Zhang et al (41) .…”
Section: Discussionmentioning
confidence: 83%
“…The increase in basal MAP in F1H and F2H offspring are consistent with the previous studies where female genitors were fed H diet for long-term, including before pregnancy until lactation (38)(39)(40) . According to Zhang et al (41) , female rats fed a H diet for 2 weeks before pregnancy until lactation showed no changes in basal MAP and blunted tachycardia baroreflex sensitivity in the F1H offspring. The difference in the basal MAP observed between our present study and Zhang et al study (41) may be due to the differential age of the F1H offspring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation